Coherent nanoscale X-ray probe for crystal interrogation at ID01, ESRF – The European Synchrotron. (5th April 2017) - Leake, S.J.; Favre-Nicolin, V.; Zatterin, E.; Richard, M-I.; Fernandez, S.; Chahine, G.; Zhou, T.; Boesecke, P.; Djazouli, H.; Schülli, T.U.
Abstract: The upgraded ID01 beamline now offers a coherent X-ray probe, 56 nm × 141 nm in size (full width half maximum), combined with access to large swathes of reciprocal space with an area detector and sufficient working distance to host various sample environments. Coherent diffraction imaging at Bragg reflections offers picometre sensitivity to lattice distortions in crystals and access to the full strain tensor, in the case where three or more non-coplanar reflections are measured. Defects may have a strong effect on the physical properties of materials. As the majority of defects produce lattice distortions, hence these can be imaged. Here we describe the instrumentation at ID01 required to produce such foci and the protocols employed to ensure reliable data acquisition. The wavefront of the incident beam must be coherent in order to observe interference. Thus the coherent probe is recovered online via ptychography on a reference structure at the beginning of every experiment, and can be executed at any time to confirm beam quality and maintain experimental consistency. Due to the small source size in the vertical direction a diffraction limited spot is achieved, whereas in the horizontal the beam size is defined by the image of the source. With the upgrade of the ESRF this asymmetry is supposed to decrease substantially, and will be accompanied by an increase in coherent flux density by a factor of 30–100. Graphical abstract: